الوظيفة الدستورية للجيش في ظل التعديل الدستوري 2020 - زياد, محمد العيد (جامعة الوادي university el-oued, 2021)
إن الدور التنموي للمؤسسة العسكرية، لا يتعارض مع المهمة الأساسية للمؤسسة العسكرية وهي الوظيفة الدفاعية، وأن المشاركة في العملية التنموية والاقتصاد، لا يخرج المؤسسة العسكرية في الجزائر من وظيفتها الأصلية. إن المؤسسة العسكرية هي أحد أهم أدوات الدولة للقيام بمهامها، كونها تحتل مكانة مركزية في قلب أي نظام، بما يؤهل الدولة للعمل على أداء وظائف بناء الأمة وشن الحرب والحماية واستخراج الموارد وتوزيعها والإنتاج، وللوقوف على أنماط الدور الاقتصادي والإجتماعي والعسكري للمؤسسة العسكرية، لا بد من التفرقة بين اعتبارين، هما مدى انخراط المؤسسة العسكرية في عملية التنمية، وتأثير ذلك الدور على عملية التحول الديمقراطي. The developmental role of the military institution does not conflict with the basic mission of the military institution, which is the defense function, and that participation in the development process and the economy does not detract from the military institution in Algeria from its original function. The military institution is one of the most important tools of the state to carry out its tasks, as it occupies a central position in the heart of any system, which qualifies the state to work on performing the functions of nation-building, waging war, protection, resource extraction, distribution and production. To find out the patterns of the economic, social and military role of the military institution, it is necessary to The distinction between two considerations, namely, the extent to which the military institution is involved in the development process, and the impact of that role on the democratic transition process.
مذكرة ماستر